Sistem Analisis Kinerja Menggunakan Metode Earned Value Untuk Proyek Pekerjaan Electrical Greenhouse di Kota Batam - Lu, Sally; Pamadi, Mulia (Jurnal Talenta Sipil, 2024)
Infrastructure projects such as greenhouse construction, are important for economic growth. Effective project control is essential, especially in terms of managing budgets and ensuring timely completion. The Earned Value (EVM) method is used in construction project control because it integrates costs, time, and work progress. This allows for the identification of potential cost and time overruns. Data on expenditures and project-related documentation are gathered for analysis. Work plans and project schedules are used to determine the value of work yet to be completed. The research findings up to the 10th month indicate that the projected total cost for completing the entire project is IDR 10.773.835.000. This leaves 8% of the total budgeted value as remaining project budget. According to the data reported in the 11th month, the projected time for completing the project is 334 days. This is approximately 304 days ahead of the planned schedule. In summary, the EVM method is a valuable tool for project control in the construction industry. It can help to identify potential cost and time overruns, and ensure that projects are completed on time and within budget.